Surgical encounter with radial nerve dysmorphogenesis in the arm: a case-based analysis and its operative implications - Naskar, Avik K.; Ganwir, Himanshu P.; Mehta, Meet A.; Atram, Vikas A.; Bhowmick, Loknath; Naktode, Ashish M. (International Journal of Research in Orthopaedics, 2025)
Radial nerve palsy is a well-recognized complication of mid-shaft humeral fractures, with an incidence of 7% to 17%. Although most cases resolve spontaneously, anatomical variations in the radial nerve may complicate surgical management and increase the risk of iatrogenic injury. We report the case of a 42-year-old male who sustained a closed mid-shaft fracture of the left humerus following a road traffic accident, presenting with partial wrist and finger drop and diminished sensation over the first webspace in the dorsum of the hand. Surgical fixation was performed via posterior approach. Intraoperatively, multiple aberrant radial nerve branches with an unusual intramuscular course were identified in the posterior aspect of arm. Careful dissection with decompression and preservation of these aberrant branches were done without tension. The patient showed progressive neurological improvement over the ensuing weeks. By two months postoperatively, there was complete recovery of motor and sensory function in the radial nerve distribution with the patient resuming normal activities. This case highlights the significance of preoperative preparedness and intraoperative vigilance in the presence of radial nerve palsy associated with humeral shaft fractures. Awareness of potential anatomical variations in the radial nerve branching pattern is critical for preventing iatrogenic injury and ensuring favorable neurological outcomes.